2018
DOI: 10.1080/13691457.2018.1540409
|View full text |Cite
|
Sign up to set email alerts
|

Applying standardisation tools in social work practice from the perspectives of social workers, managers, and politicians: a Swedish case study

Abstract: This article reports findings from a case study of the practical application of a standardisation tool in everyday social work practice. The example tool used herein is the Swedish version of the UK-based Integrated Children's System, which in Sweden is known as Children's Needs in Focus (Barns Behov i Centrum; BBIC). The study analyses group and individual interviews with social workers, managers and politicians using concepts from implementation research and the micro-sociological concept of accounts. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…For example, the literature on street-level bureaucracy highlights organizational factors such as resource limitations, policy directives, program content, and governance mode (e.g., new public management [NPM]; Fuertes & Lindsay, 2016). Skillmark and Oscarsson (2020) identified organizational factors that explained increasing deviance from a standard over time.…”
Section: Evidence-based Standardization and Frontline Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the literature on street-level bureaucracy highlights organizational factors such as resource limitations, policy directives, program content, and governance mode (e.g., new public management [NPM]; Fuertes & Lindsay, 2016). Skillmark and Oscarsson (2020) identified organizational factors that explained increasing deviance from a standard over time.…”
Section: Evidence-based Standardization and Frontline Practicesmentioning
confidence: 99%
“…The literature focuses extensively on the challenges of implementing evidence-based standards in frontline service delivery and professional work (Bergmark et al, 2018;Gray et al, 2009;Høybye-Mortensen, 2013;Ponnert & Svensson, 2016;Skillmark & Oscarsson, 2020;White et al, 2008). A related debate concerns whether standards should be implemented with high fidelity or be adapted to local needs (Damschroder et al, 2009;Durlak & DuPre, 2008).…”
mentioning
confidence: 99%
“…In addition to the need for further education in the field of ICT, many authors point to the need for educating social workers in other areas [47][48][49][50][51]. These could be closely linked to the concept of sustainability, which would help them better manage the solution of social situations in relation not only to clients but also to themselves because social workers work in (a) precarious, (b) complex, and (c) managerially oriented work environment [49,52,53], which puts pressure on their competencies, including the digital ones.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of respondents (59) stated that they did not know or did not use such a program. Also, other programs, such as registration database systems, were considered unimportant by a large part of the respondents (53).…”
Section: The Quantitative Part Of the Researchmentioning
confidence: 99%
“…Research on decision-making tools has shown how they can be found supportive (Gillingham et al 2017) but also time-consuming (Høybye-Mortensen 2015) and result in short cuts (Broadhurst et al 2009) and significant differences between the informal and formal practice, prompting caution in the development and implementation of tools (Gillingham and Humphreys 2010). They would benefit from being fitted to the users' relationship with their clients (Skillmark and Oscarsson 2020) and it may be possible to preserve discretion through a relational approach, although this decreases the possibility for accountability (De Witte et al 2016).…”
Section: Literature On Standardization and Copingmentioning
confidence: 99%